Integrative framework for riparian buffer management for independent oil palm plantation - Maria Roswita Kartika Sari Bawono (Journal of Agrosociology and Sustainability, 2026)
Background: Riparian buffers play a critical role in maintaining water quality, preventing erosion, and conserving biodiversity in oil palm landscapes. However, independent smallholders, who manage approximately 40% of Indonesia’s oil palm plantation area, face constraints in riparian management due to limited land, capital, and technical capacity. Although riparian zones are legally protected, policy implementation remains weak. Meanwhile, the traditional local wisdom system in Jambi has demonstrated ecological and socio-economic benefits. This study aims to develop an integrative riparian management framework for independent oil palm smallholders in Jambi. Methods: This study employed a literature-based approach using national regulations, Best Management Practices (BMPs), and literature on riparian restoration and local customary practices. Data were analyzed through content analysis to identify key elements and develop an adaptive management framework. Findings: Formal regulations provide legal legitimacy for riparian protection but remain inadequately implemented. BMPs offer practical guidance, including buffer-zone delineation, native-species revegetation, and chemical-free management. The local wisdom system strengthens compliance through customary norms and shared community benefits. Conclusion: Adaptive co-management that integrates legal, technical, and local knowledge dimensions can strengthen social legitimacy and ecological resilience, supporting sustainable riparian management by independent oil palm smallholders. Novelty/Originality of this article: This study proposes an integrative riparian management framework that combines government regulations, technical management guidelines, and the local wisdom within an adaptive co-management approach, providing a socially legitimate and ecologically resilient strategy for sustainable riparian management.